Intensive training programme for ultrasound-guided minimally invasive synovial tissue biopsy on knees and wrists in different phases of inflammation - Maria-Antonietta D’Agostino; Maria Sole Chimenti; Roberto Caporali; Giuliana Guggino; Francesco Ciccia; Elisa Gremese; Barbara Tolusso; Stefano Alivernini; Marco Gessi; Pietro Rubortone; Lavinia Agra Coletto; Laura Bui; et al. (RMD Open)
Objectives To develop an intensive training programme for ultrasound (US)-guided synovial tissue (ST) biopsy on knees and wrists in inflammatory arthritis and to assess the learning curve, patient tolerability, sample quality and trainees’ expectations.Methods Active or remission rheumatoid arthritis patients were enrolled. Nine trainees joined the 4-month programme in a centre experienced in performing US-guided ST biopsies consisting of four sequential phases: (1) observation, (2) performance of guided step-by-step phases, (3) execution of the whole procedure on paired joints (knees or wrists) of the same patient in parallel with the trainer and (4) performance of the procedure autonomously. Sample representativity was assessed by histology, and procedure-related adverse events were recorded. Before and after the programme, trainees’ expectations and perceptions were collected.Results 328 ST biopsy procedures were included. The rate of trainees’ informative samples was: (1) comparable to the trainers in active and remission knees, but lower in active wrists (70% for trainees vs 100% for trainers, p=0.06) in phase 3; (2) excellent on active knees and wrists (91.9% and 90.9% respectively) but lower (77.6%, p=0.0089) on remission knees in phase 4. Procedures performed by trainees did not affect patient tolerability. Trainees’ expectations about procedure-related invasiveness and pain infliction decreased while the difficulty of procedure execution on active wrists and remission knees remained perceived as moderately difficult.Conclusions This intensive training programme develops advanced skills in the performance of US-guided ST biopsy on knees and wrists, yielding high-quality specimens available for basic and translational studies on inflammatory joint diseases.